Practical R&D project prioritization - Brenner, Merrill S.
Merrill S. Brenner outlines a systematic project selection process used at Air Products.
By providing a better approach to dealing with limited resources, this process allows more of the best projects to be completed.
Allocation of scarce resources among a multitude of diverse projects is a continual problem facing R&D management. A systematic project selection process used at Air Products identifies and builds consensus around the key issues for success, communicates these factors to improve project proposals, and helps to extend limited funding to maximize project progress and completion. Decision-makers select and weight criteria in a structured framework based upon the analytic hierarchy process. Project champions then propose their projects within that framework. Project strengths and weaknesses are clearly identified by using profiles of the project ratings for each criterion. Thus, strong projects are fully funded, weak projects are not funded, and intermediate projects are funded to resolve weaknesses.
Keywords: R&D project